2018
DOI: 10.1007/s11695-018-3594-0
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Hiatal Hernia Repair Is more Common in Laparoscopic Sleeve Gastrectomy than During Laparoscopic Roux-en-Y Gastric Bypass: an Analysis of 130,772 Cases

Abstract: Obesity is associated with the development of gastroesophageal reflux disease (GERD) and hiatal hernia (HH). This study aimed to assess practice patterns regarding concomitant HH repair (HHR) during laparoscopic sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB). The incidence of concomitant HHR with LSG or LRYGB was analyzed using the 2015 Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program database. One hundred thirty thousand, seven hundred seventy-two patients underwent R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…This represents a significant percentage of weight loss surgery patients who have paraesophageal hernias repaired at the time of their operation, but based on reported rates of hiatal hernias in patients having weight loss surgery this indicates that a significant number of patients do not have their hiatal hernia repaired during their index weight loss surgery. Particularly, small hiatal hernias may not be repaired during the index operation, especially in patients having a gastric bypass compared to sleeve gastrectomy and, thus, may set the patient up for subsequent complications at a remote point from their operation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a significant percentage of weight loss surgery patients who have paraesophageal hernias repaired at the time of their operation, but based on reported rates of hiatal hernias in patients having weight loss surgery this indicates that a significant number of patients do not have their hiatal hernia repaired during their index weight loss surgery. Particularly, small hiatal hernias may not be repaired during the index operation, especially in patients having a gastric bypass compared to sleeve gastrectomy and, thus, may set the patient up for subsequent complications at a remote point from their operation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, small hiatal hernias may not be repaired during the index operation, especially in patients having a gastric bypass compared to sleeve gastrectomy and, thus, may set the patient up for subsequent complications at a remote point from their operation [11].…”
Section: Discussionmentioning
confidence: 99%
“…50 A large database (the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program [MBSAQIP]) query encompassing over 39 000 patients showed that only 10% of the cases underwent concomitant hiatal hernia repair. 51 Curiously, a steady but slow increase in the percentage of patients that undergo a concomitant hiatal repair has been noticed. 52 This may reflect the low risk for post-operative GERD.…”
Section: Introductionmentioning
confidence: 99%
“…2 Obesity is an independent risk factor for hh and gerD. [3][4][5] increase of body mass index (BMi) will upsurge the risk of hh's incidence, gerD symptoms and erosive esophagitis (ee), regardless of demographic features and dietary intake. 2 The prevalence of gerD in patients with obesity ranges from 37% to 72%, especially in morbid obese patients' candidate to bariatric surgery.…”
mentioning
confidence: 99%
“…2 The prevalence of gerD in patients with obesity ranges from 37% to 72%, especially in morbid obese patients' candidate to bariatric surgery. [2][3][4][5] Concomitant hhr during bariatric surgery is gaining worldwide popularity, 4 following international guidelines of SageS recommending the repair of all hiatus defects during any bariatric procedure, 5 especially during laparoscopic sleeve gastrectomy (LSg). LSg has higher reported gerD rates and proton pump inhibitor (PPi) use; other indications for concomitant treatment are prevention of postoperative acid/ biliary gastroesophageal reflux and of the intrathoracic migrations (iTM) of the operated stomach, even in asymptomatic patients, especially with large hh.…”
mentioning
confidence: 99%